FerryBox-integrated membrane-based pCO2, temperature, salinity, oxygen, chlorophyll, turbidity and pH measurements of BU-C-2205 during RV Burchana cruise - Lara Luitjens; Dagmar Daehne; Cordula Berkenbrink; Andreas Wurpts (PANGAEA, 2025)
The submitted data were collected with a FerryBox-Device on RV Burchana in the transitional and coastal waters of Lower Saxony, Germany. It contains data for temperature, salinity, pH, chlorophyll, oxygen, turbidity and carbon dioxide partial pressure (pCO2) at a water depth of approximately 1.3 m. Within the Carbostore project, totally 8 measurement campaigns were carried out in the years 2021 to 2023. The data is reprocessed and related to a 60 s period. In order to obtain a complete (but rough) overview of the pCO2 situation in this area, values outside the calibration limits (200-1000 μatm) were retained. Dissolved oxygen measurements were corrected by temperature and salinity. The sensors are regularly calibrated, maintained and replaced if necessary. The files are named according to the project, the year and the month of the campaign.